Psalmės Lietuvos Didžiosios Kunigaikštystės giesmynuose. XVI amžius: nuo Nesvyžiaus Katekizmo iki lietuviškųjų Merkelio Petkevičiaus vertimų - Pociūtė, Dainora (Literatūra, 2015)
The article aims at presenting and discussing the earliest reformed publications in the Grand Duchy of Lithuania (16 c.), featuring versified translations of Biblical psalms designed for the church repertoire. It also aspires to indicate the trends of this repertoire, adoption and authorship of the texts, as well as to describe them in relation to the most important Polish psalm books of the 16th century.The article focuses on extremely rare collections of the Lithuanian Reformed Church texts that presently exist as unique copies stored in different libraries in Sweden, Switzerland, and Poland. The books comprise: the Nesvyžius Catechism (1563), the Nesvyžius Song Book for Women (1564), Vilnius catechisms of 1581, 1594, and 1598, and Merkelis Petkevičius’ Catechism (1598), the first Lithuanian reformed publication based on the four Polish editions enumerated above.The two Hymnbooks published in 1553–1554 in Nesvyžius include the first 58 versified psalm translations in the Grand Duchy of Lithuania. The editors of the Nesvyžius Catechism (Szymon Budny, Martin Czechowicz, Tomasz Falkonius and others) used some early individual psalm translations by Polish authors. However, the bulk (43) of the psalm translations in the Nesvyžius Catechism were made by local Lithuanian authors and were published in this version in Polish for the first time. The second official collection of Reformed Church texts was published in Vilnius in 1581. It presented translations of 90 psalms. Although the publishers of the Vilnius Catechism, who from early on declared to be antitrinitarian, dissociated themselves from the Nesvyžius Catechism, they reprinted all but one psalm from that edition. The article establishes that the basis of the updated repertoire of the Vilnius Catechism of 1581 consisted of 14 of Jakub Lubelczyk’s and 8 Jan Kochanowski’s psalms. Thus, the 1581 Vilnius Catechism testifies to the fact that Kochanowski’s psalms, a collection of which had just come out in 1579, were first published in the Grand Duchy of Lithuania on the initiative of the reformers and it was not until later that they were included into Polish protestant Piotr Artomiusz’ hymnbooks published in Prussia (Toruń). In the reprinted edition of the Vilnius reformed Catechism of 1594 the corpus of the psalm book was not altered at all. The translator of the first Lithuanian psalms, Merkelis Petkevičius, who published a bilingual collection of Lithuanian church texts featuring 41 psalms, used this particular edition. He translated 40 texts from the Vilnius Catechism of 1594 in a row with a few omissions.Most of the Lithuanian psalms originate from the repertoire of the Nesvyžius period and only 13 of them can be associated with the repertoire introduced by the Vilnius Catechism of 1581. Thus, the conclusion is made that both Lithuanian and Polish psalm repertoires in the 16th century Grand Duchy of Lithuania were dominated by the local repertoire put forward by the reformers and established by the editors of the Nesvyžius Catechism. The article discusses different aspects of the psalm authorship in greater detail.